Combination anthelmintic/antioxidant activity against Schistosoma Mansoni - Gouveia, Maria João (2020)
Schistosomiasis is a major neglected tropical disease. Treatment for schistosomiasis with praziquantel (PZQ), which is effective against the parasite, by itself is not capable to counteract infection-associated disease lesions including hepatic fibrosis. There is a pressing need for novel therapies. Due to their biological properties, antioxidant biomolecules might be useful in treating and reverting associated pathological sequelae. Here, we investigated a novel therapy approach based on a combination of anthelmintic drugs with antioxidant biomolecules. We used a host-parasite model involving Bioamphalaria glabrata and newly transformed schistosomula (NTS) of Schistosoma mansoni. For in vitro drug screening assays, was selected several antioxidants and evaluated not only antischistosomal activity but also ability to enhance activity of the anthelmintic drugs praziquantel (PZQ) and artesunate (AS). The morphological alterations induced by compounds alone/combined were assessed on daily basis using an inverted and automated microscope to quantify NTS viability by a fluorometric-based method. The findings indicated that not only do some antioxidants improve antischistosomal activity of the two anthelmintics, but they exhibit activity per se, leading to high mortality of NTS post-exposure. The combination index (CI) of PZQ + Mel (CI = 0.80), PZQ + Resv (CI = 0.74), AS + Resv (CI = 0.34), AS + NAC (CI = 0.89), VDT + Flav (CI = 1.03) and VDT + Resv (CI = 1.06) reveal that they display moderate to strong synergism. The combination of compounds with discrete mechanisms of action might provide a valuable adjunct to contribution for treatment of schistosomiasis-associated disease.